Assessing Epilepsy Treatment Adherence and Factors Contributing to Adherence among People with Epilepsy in Paung Township - Oo, San; Shwe, Zarni Myint; Lin, Htet Htet (International Journal of Epilepsy, 2024)
Objective This study evaluates medication adherence among epilepsy patients at public health facilities in Paung Township, Mon State, Myanmar, using both quantitative and qualitative methods to explore influencing factors.Materials and Methods This cross-sectional study in Paung Township involved 72 epilepsy patients aged 12 years and older, receiving antiseizure medications for at least 6 months. Quantitative data were collected through questionnaires and the Morisky Medication Adherence Scale (MMAS-8), while qualitative insights were obtained from three focus group discussions involving patients and family members.Results The study involved 72 people with epilepsy (PWE) in Paung Township, Myanmar, examining baseline characteristics, treatment services, perceptions, and adherence. The majority were young adults, and 87.5% lived in rural areas. Phenobarbital was the primary medication, and 94.4% received free medications. Most reported >50% seizure reduction and 75% attended follow-ups regularly. Overall, 59.7% demonstrated high adherence. Negative attitudes toward missing medication were prevalent among 90.3% of patients, and this was significantly associated with high adherence (p < 0.05). Family support (97.2%) and the convenience of accessing health facilities for medication were widely reported but did not show a significant association with the level of medication adherence. The qualitative findings affirmed satisfaction with health care services, minimal transportation challenges, reduced seizures, manageable side effects, and strong family support. Regular follow-ups significantly predicted adherence.Conclusion Medication adherence among epilepsy patients in Paung Township was assessed using the MMAS-8, revealing high adherence in nearly 60% of participants. Regular follow-up appointments were significantly correlated with adherence, while negative attitudes toward missed doses and side effects influenced adherence. Patients expressed satisfaction with free medication services, convenience, and reduced seizure frequency.
Keywords: epilepsy; seizures; medication adherence; Morisky Medication Adherence Scale